Indicadores de perda de qualidade em grãos de soja - Sousa, Janaina Rosa de (2015)
Although all the technology available to Brazilian agriculture, qualitative and quantitative losses arising during the process of post-harvest grain, are not well controlled. Scale the losses during storage is crucial in order to take the proper procedures to minimize them. Therefore, in this study included three experiments: the first evaluated the physical quality, nutritional quality, chemical quality and sanitary quality of soybean defects; the second evaluated the loss of physical quality, nutritional and sanitary quality of soybean stored for a period of 210 days under laboratory conditions (30 ° C and 46% RH) and controlled (23 ° C and 50% RH), subject to infestation Lasioderma serricorne; in the third it was evaluated the acidity in grains with different quality frameworks in commercial soy pattern. At first experiment, there were the following quality analysis: water content, weight of 100 grains, crude protein and ether extract, acid value, fungal incidence and detection of aflatoxins (B1, B2, G1 and G2). It was observed higher average crude protein in damaged kernels, burned, moldy and fermented. There were increases in protein content and acidity levels with advancing deterioration of the grains. For the evaluation of losses, was evaluated monthly water content, the density apparent electrical conductivity crude protein and ether extract internal and external infestation. Analyses of sanity and commercial classification were performed initially and at 210 days. The natural environment caused greater loss of quality in the grain during storage, regardless of the level of infestation. To check the alcoholic acid number in soybeans were evaluated water content, bulk density, the alcoholic acid number of the crude protein and lipids and electrical conductivity. For all crops assessed was increased acidity as the worst trading environment. In comparing the two stratifications within each frame there was significance in all parameters evaluated quality, with higher averages presented in the second stratum. It can be concluded that the alcoholic acid number also corresponds to the electrical conductivity and consequently damaged with the total grains.